LEGAL EFFORTS OF SPECIAL DETACHMENT 88 ANTI-TERROR INVESTIGATORS, POLICE OF THE REPUBLIC OF INDONESIA AFTER THE DECISION OF THE CONSTITUTIONAL COURT NUMBER 130/PUU-XIII/2015 - JUANRICO ALFAROMONA SUMAREZS TITAHELU (Sekolah Tinggi Ilmu Hukum Awang Long, 2021)
A process of investigating the existence of a criminal act, especially a criminal act of terrorism, of course, the investigators of Special Detachment (Densus) 88 Anti-Terror Police will seek and collect preliminary evidence based on the provisions, namely at least two pieces of evidence and if all have been collected, the next process is conducting an investigation. Prior to entering into the investigation process, investigators are required to issue a notification letter for conducting an investigation (Surat Pemberitahuan Dilaksanakan Penyidikan/SPDP) to the Prosecutor's Office and the families of suspected terrorists. Prior to the Decision of the Constitutional Court of the Republic of Indonesia Number 130/PUU/XIII/2015, investigators were given 21 days but after this decision was issued and enforced, investigators were only given 7 days to issue the SPDP. So that this becomes an obstacle in terms of collecting preliminary evidence by Investigators of the Anti-Terror Detachment 88 Police because our country has many islands separated by the sea and the geographical conditions of an area that are different from other regions, so inevitably investigators must coordinate with other parties. The Prosecutor's Office is related to this matter, but sometimes the Prosecutor still adheres to the decision of the Indonesian Constitutional Court. So the problem that arises is what legal action was taken by the Investigators of the Anti-Terror Detachment 88 of the Police in issuing the SPDP after the Decision of the Constitutional Court of the Republic of Indonesia Number 130/PUU/XII/2015. The results of the research show that legal efforts in the form of making a cooperation agreement between the Attorney General and the National Police Chief, and revising the Decree of the Head of the Special Detachment 88 Anti-Terror Number: Kep/11/IV/2018, can be an effective solution for the investigators of Densus 88 Anti-Terror Polri to implement the Decision of the Constitutional Court of the Republic of Indonesia No. 130/PUU-XIII/2015.